2013
DOI: 10.1017/s031716710001369x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Intracranial Stenosis and Microemboli in Asymptomatic Carotid Stenosis

Abstract: With more intensive medical therapy, the risk of stroke or death in patients with asymptomatic carotid stenosis is now so low that most patients will not benefit from endarterectomy or stenting 1 . It is therefore important to have methods to identify the small proportion who could benefit from intervention 1,2 , or who may require special consideration in choice of medical therapy. We have previously reported that carotid plaque area 3 , microemboli on transcranial Doppler 4,5 (TCD), and carotid plaque ulcera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Intracranial stenosis is more common in Asian patients and in diabetics 69, 70 . The Stenting and Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial 71 reported in 2014 that intensive medical therapy that included lifestyle modification was more efficacious than stenting for intracranial stenosis.…”
Section: Intracranial Stenosismentioning
confidence: 99%
“…Intracranial stenosis is more common in Asian patients and in diabetics 69, 70 . The Stenting and Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial 71 reported in 2014 that intensive medical therapy that included lifestyle modification was more efficacious than stenting for intracranial stenosis.…”
Section: Intracranial Stenosismentioning
confidence: 99%
“…Caplan has suggested4 that microatheroma may account for some of small vessel disease. This may be more common in diabetes mellitus, another cause of ‘small vessel disease’, and which is associated with a higher prevalence of intracranial stenosis of larger arteries 5. Recently he pointed out6 that conditions ‘that affect small arterioles and capillaries originating from peripheral branches of the large intracranial arteries that supply blood to the more superficial regions of the brain’ are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we knew there are some subtypes of stroke in literatures and patients with diabetes are more likely to have intracranial stenosis. 27 The ischemic stroke still accounted for most of the stroke in China 7 although in general the hemorrhagic strokes in Chinese are common than western population. Unfortunately, in the present study we do not have sufficient information to satisfactorily classify the sub-types of stroke.…”
Section: Discussionmentioning
confidence: 99%